Influence of Cutting Fluid Application Frequency in Micromilling Cutting Forces - Deborah De Oliveira; Milla Caroline Gomes; Aline Gonçalves dos Santos; Marcio Bacci Da Silva (International Journal of Engineering Materials and Manufacture, 2021)
Micromachining allows the production of parts and components on a micro scale with high precision and has become a key process to meet the growing demand for micro parts and micro components. To meet the quality requirements of the generated surfaces and reduce the cutting forces, strategies have been analysed, such as the use of the cutting fluid. Therefore, this research aimed to verify the effect of the frequency of the use of cutting fluid during the micro-milling of the Inconel 718 alloy. For this purpose, an ultra-refined cemented carbide micro end mill coated with (Al, Ti) N and 400 µm in diameter was used. A spindle speed of 20,000 rpm, a cutting speed of 13.8 m/min, a feed per tooth of 5 µm/tooth and an axial depth of cut of 40 µm were used as cutting parameters. Two frequencies of application of the cutting fluid were evaluated, corresponding to the flow rate of 40.7 and 270.0 ml/ h, in addition to the dry test. To measure the cutting forces, a Kistler dynamometer with operating range of -5 kN to +10 kN was used. In addition, the process simulation was performed using the AdvantEdge software by ThirdWave Systems. The results showed that the higher flow of the cutting fluid provided lower cutting forces and that, in dry machining, the cutting force increased significantly during the machining of a slot.